Technology education goal defining framework - Metsärinne, Mika (Australasian Journal of Technology Education, 2023)
The purpose of this article is to develop theoretical framework for defining technology education (TE) goals. First, approaches to technocratic determinism, the determinism of nature, voluntarism and aestheticism of technology have been considered within the same framework. Second, four alternative definitions for technology (Freenberg, 2007) have been applied within these approaches. Instrumentalism emphasises learners’ creative product production. The critical theory of technology emphasises cultural impact of learners’ product using and learning design knowledge. Determinism emphasises learner technology understanding and substantivism learner technology appraising. Third, analysing by the approaches, a sample of the TE goals of Finnish craft student teachers (n=100) wanted to develop for junior- and high school teaching and learning is described. The goals and the corresponding learning materials showed that they were evenly distributed across all the approaches. The framework provides comprehensive thinking ways for defining TE goals and curriculum.